Anti‐adhesion activity of thyme (Thymus vulgaris L.) extract, thyme post‐distillation waste, and olive (Olea europea L.) leaf extract against Campylobacter jejuni on polystyrene and intestine epithelial cells. (24th September 2015) - Šikić Pogačar, Maja; Klančnik, Anja; Bucar, Franz; Langerholc, Tomaž; Smole Možina, Sonja
Abstract: BACKGROUND: In order to survive in food‐processing environments and cause disease, Campylobacter jejuni requires specific survival mechanisms, such as biofilms, which contribute to its transmission through the food chain to the human host and present a critical form of resistance to a wide variety of antimicrobials. RESULTS: Phytochemical analysis of thyme ethanolic extract (TE), thyme post‐hydrodistillation residue (TE‐R), and olive leaf extract (OE) using high‐performance liquid chromatography with photodiode array indicates that the major compounds in TE and TE‐R are flavone glucuronides and rosmarinic acid derivatives, and in OE verbascoside, luteolin 7‐ O ‐glucoside and oleuroside. TE and TE‐R reduced C. jejuni adhesion to abiotic surfaces by up to 30% at 0.2–12.5 µg mL −1, with TE‐R showing a greater effect. OE from 3.125 to 200 µg mL −1 reduced C. jejuni adhesion to polystyrene by 10–23%. On the other hand, C. jejuni adhesion to PSI cl1 cells was inhibited by almost 30% over a large concentration range of these extracts. CONCLUSION: Our findings suggest that TE, the agro‐food waste material TE‐R, and the by‐product OE represent sources of bioactive phytochemicals that are effective at low concentrations and can be used as therapeutic agents to prevent bacterial adhesion. © 2015 Society of Chemical Industry